2008
DOI: 10.1152/ajpendo.00312.2007
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces hyperacetylation of histones at the MEF2 site on theGlut4promoter and increases MEF2A binding to the site via a CaMK-dependent mechanism

Abstract: Mukwevho E, Kohn TA, Lang D, Nyatia E, Smith J, Ojuka EO. Caffeine induces hyperacetylation of histones at the MEF2 site on the Glut4 promoter and increases MEF2A binding to the site via a CaMK-dependent mechanism. Am J Physiol Endocrinol Metab 294: E582-E588, 2008. First published January 15, 2008 doi:10.1152/ajpendo.00312.2007.-This study was conducted to explore the mechanism by which caffeine increases GLUT4 expression in C2C12 myotubes. Myoblasts were differentiated in DMEM containing 2% horse serum for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 35 publications
5
46
0
1
Order By: Relevance
“…Our results suggest that caffeine administration restored Glut4 expression in the elderly group, but it was not able to increase Glut4 expression above a maximal level in the 12 M group. The mechanism by which caffeine increases Glut4 expression is still unclear, but the effect appears to be extant to several cell types: rat skeletal muscle primary cultures (Egawa et al 2009) and myoblasts (Mukwevho et al 2008), although contrasting results have been obtained in adipose tissue cells where caffeine suppressed insulininduced Glut4 translocation (Akiba et al 2004). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that caffeine administration restored Glut4 expression in the elderly group, but it was not able to increase Glut4 expression above a maximal level in the 12 M group. The mechanism by which caffeine increases Glut4 expression is still unclear, but the effect appears to be extant to several cell types: rat skeletal muscle primary cultures (Egawa et al 2009) and myoblasts (Mukwevho et al 2008), although contrasting results have been obtained in adipose tissue cells where caffeine suppressed insulininduced Glut4 translocation (Akiba et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, caffeine has also been implicated in skeletal muscle regulation of glucose and lipid metabolism. Caffeine stimulates insulin-independent muscle glucose transport (Wright et al 2004;Jensen et al 2007) and increases Glut4 mRNA and/or protein expression and fatty acid metabolism (Mukwevho et al 2008), having metabolic effects similar to the ones of 5′-AMP activated protein kinase (AMPK).…”
Section: Introductionmentioning
confidence: 99%
“…First, Smith et al (33) infected C 2 C 12 myotubes with adenoviruses that expressed constitutively active (CA) or dominant negative (DN) CaMK IV and observed a twofold increase of Glut4 promoter-bound MEF2A in the CA CaMK IV-expressing myotubes compared with the DN-expressing controls. Second, Mukwevho et al (25) incubated C 2 C 12 myotubes with caffeine to activate CaMK II and found an ϳ2.2-fold increase in the amount of MEF2A that bound to the Glut4 gene compared with untreated controls, but inclusion of a CaMK II inhibitor (KN93) in the culture medium abolished the increase by caffeine. In both studies, CaMK activation also increased GLUT4 expression.…”
mentioning
confidence: 99%
“…Once bound, they prevent new activation of the subunit but have little effect on the activity of subunits that have already been activated by phosphorylation (102,110). KN93 has been widely used to inhibit CaMKII activity in cultured muscle cells, in isolated muscles, and in live animals (8,73,78). It has, however, been reported that, in addition to inhibiting CaMKII, KN93 also inhibits voltage-dependent K ϩ currents (87) and L-type calcium channel activity (30).…”
Section: Mechanism Of Camk Activation In Skeletal Muscle During Exercisementioning
confidence: 99%
“…Mukwehvo et al (73) explored the mechanism by which caffeine increased GLUT4 expression in C 2 C 12 myotubes and tested whether these mechanisms were also CaMKII dependent. They used KN-93 to inhibit CaMKII and dantrolene to prevent Ca 2ϩ release from the sarcoplasmic reticulum.…”
Section: Camk Activation and Mef2-dependent Gene Expressionmentioning
confidence: 99%